Passive cavitation mapping for monitoring ultrasound therapy - Gyöngy, M (2010)
Cavitation is a phenomenon present during many ultrasound therapies, including the thermal ablation of malignant tissue using high intensity focused ultrasound (HIFU). Inertial cavitation, in particular, has been previously shown to result in increased heat deposition and to be associated with broadband noise emissions that can be readily monitored using a passive receiver without interference from the main ultrasound signal. The present work demonstrates how an array of passive receivers can be used to generate maps of cavitation distribution during HIFU exposure, uncovering a new potential method of monitoring HIFU treatment. Using a commercially available ultrasound system (z.one, Zonare, USA), pulse transmission can be switched off and data from 64 elements of an array can be simultaneously acquired to generate passive maps of acoustic source power. For the present work, a 38 mm aperture 5-10 MHz linear array was used, with the 64 elements chosen to span the entire aperture. Theory and simulations were used to show the spatial resolution of the system, the latter showing that the broadband nature of inertial cavitation makes passive maps robust to interference between cavitating bubbles. Passive source mapping was first applied to wire scatterers, demonstrating the ability of the system to resolve broadband sources. With the array transversely placed to the HIFU axis, high-resolution passive maps are generated, and emissions from several cavitating bubbles are resolved. The sensitivity of passive mapping during HIFU exposure is compared with that of an active cavitation detector following exposure. The array was then placed within a rectangular opening in the centre of the HIFU transducer, providing a geometric setup that could be used clinically to monitor HIFU treatment. Cavitation was instigated in continuous and disjoint regions in agar tissue mimicking gel, with the expected regions of cavitation validating the passive maps obtained. Finally, passive maps were generated for samples of ox liver exposed to HIFU. The onset of inertial cavitation as detected by the passive mapping approach was found to provide a much more robust indicator of lesioning than post-exposure B-mode hyperecho, which is in current clinical use. Passive maps based on the broadband component of the received signal were able to localize the lesions both transversely and axially, however cavitation is generally indicated 5 mm prefocal to the lesions. Further work is needed to establish the source of this discrepancy. It is believed that with use of an appropriately designed cavitation detection array, passive mapping will represent a major advance in ultrasound-guided HIFU therapy. Not only can it be utilized in real-time during HIFU exposure, without the need to turn the therapeutic ultrasound field off, but it has also been shown in the context of the present work to provide a strong indicator of successful lesioning and high signal-to-noise compared to conventional B-mode ultrasound techniques.